A Decade of Soft Computing Approaches in Power System Investment Planning. Issue 1 (May 2021) - Yaakob, S B; Rahman, A S F; Mukhtar, N M; Yaakob, M N; Arbaiy, N; Lin, P-C
Abstract: This paper opens up an issue regarding to power system investment planning. In order to obtain a sustainable electricity supply, the power outage should be minimized. Maintenance cost plays as an essential element in investment planning, therefore misdirect investment should be avoided. Since soft computing can solved this problem, this paper offers a review in solving investment planning problem through such approaches. The main objective of this paper is to examine the concept and findings by the researchers in power system investment planning problem. Besides, this paper will highlight the most relevant contributions and limitations that can be improve in the other research. Finally, this paper will be pointed out some trends in power system investment planning problem.